Multiaxial Fatigue-Life Prediction of Railway Axles with Consideration of Braking Effects - Theingi Nwe; Monsak Pimsarn (My University, 2023)
Ensuring safety in the design of railway infrastructure and rolling stock is a critical aspect of railway operations.Railway axles are subjected to fluctuating bending and torsion loads, which often lead to the development of plastic stresses in the vicinity of fillets and notches, even though they are designed to withstand nominal elastic loads.This study aims to provide an accurate fatigue-life prediction for a motor bogie axle, taking into account the braking effects in conjunction with press fitting and the influence of masses in motion on the axle.Initially, the stress and deflection of the axle under combined loadings are calculated in accordance with the EN 13104 standard.Subsequently, a comparative simulation analysis is conducted using ABAQUS commercial software, with particular emphasis on specific loading conditions.A strainbased approach is employed to estimate fatigue life under multiaxial loading and variable amplitude overloading scenarios, utilizing fe-safe commercial fatigue analysis software.The results reveal a strong correlation between the theoretical and finite element analyses.The braking effects are found to reduce fatigue life by 50% compared to the influences of press fitting combined with masses in motion.This research highlights the significance of considering braking effects in fatigue-life predictions of railway axles to ensure safe and robust design.
Keywords: Bogie; Fatigue limit; Axle load; Mechanical stress and fatigue analysis